(untitled) (Brazilian Journal of Health Research, 2019)
Introduction: Nowadays, health is increasingly addressed in social networks. Its use in dentistry, for example, has been widespread in health services; consequently, there is a larger number of posts that are not in compliance with the Code of Dental Ethics, and it brings great challenges to professionals and their class councils. Objective: Analyzing dental professionals and clinics’ profiles on Facebook based on ethical aspects determined by the Code of Dental Ethics and by the Consumer Protection Code. Methods: In total, 50 pages and dental clinic profiles, as well as 50 dentists from ES were identified on Facebook from 2013 to June 2017. These profiles were revisited in January 2019 in order to generate a comparative table of posts. An analysis protocol based on six categories was used according to the Code of Dental Ethics and to the Code of Consumer Protection. Results: Infringements related to professional negligence, advertisements, unauthorized patient exposure, professional fees, giveaways, promotions and services were found in the profiles. The absence of specific articles in the Code of Ethics about the conduct of dental professionals in social networks exposed the opened space for the committed infractions. The topic is addressed in general terms, it refers to any kind of mass media. Conclusion: The role of the Regional Council of Dentistry in supervising social networks becomes imperative, it adds to dentists’ full knowledge about the Code of Dental Ethics, as well as to the duty to report irregularities.